Persepsi Peserta Didik Tentang Pembelajaran Berbasis Proyek Dalam Meningkatkan Keterampilan Kolaborasi di Kelas V - Desy Erviana; Widya Kusumaningsih; Nuruliarsih (DIKDAS MATAPPA: Jurnal Ilmu Pendidikan Dasar, 2024)
This study aims to explore students' perceptions of project-based learning in enhancing collaboration skills in 5th grade at SDN Sambirejo 02. The research method used is a descriptive qualitative approach. The research participants consisted of 24 5th-grade students. The research findings indicate that students have a positive perception of project-based learning. They consider this type of learning as an opportunity to collaborate with their classmates, develop listening skills, share ideas, work in teams, and appreciate team contributions. This research provides a deeper understanding of students' perceptions of project-based learning and its implications in enhancing collaboration skills in 5th grade at SDN Sambirejo 02.